The integration of process design and control - Seferlis, Panagiotis, 1967-; Georgiadis, Michael C. (Amsterdam ; Boston : Elsevier, 2004)
Traditionally, process design and control system design are performed sequentially. It is only recently displayed that a simultaneous approach to the design and control leads to significant economic benefits and improved dynamic performance during plant operation. Extensive research in issues such as 'interactions of design and control', 'analysis and design of plant wide control systems', 'integrated methods for design and control' has resulted in impressive advances and significant new technologies that have enriched the variety of instruments available for the design engineer in her endeavour to design and operate new processes. The field of integrated process design and control has reached a maturity level that mingles the best from process knowledge and understanding and control theory on one side, with the best from numerical analysis and optimisation on the other. Direct implementation of integrated methods should soon become the mainstream design procedure. Within this context 'The Integration of Process Design and Control', bringing together the developments in a variety of topics related to the integrated design and control, will be a real asset for design engineers, practitioners and researchers. Although the individual chapters reach a depth of analysis close to the frontier of current research status, the structure of the book and the autonomous nature of the chapters make the book suitable for a newcomer in the area. The book comprises four distinct parts: Part A: Process characterization and controllability analysis Part B: Integrated process design and control & dashv; Methods Part C: Plant wide interactions of design and control Part D: Integrated process design and control & dashv; Extensions By the end of the book, the reader will have developed a commanding comprehension of the main aspects of integrated design and control, the ability to critically assess the key characteristics and elements related to the interactions between design and control and the capacity to implement the new technology in practice. * This book brings together the latest developments in a variety of topics related to integrated design and control. * It is a valuable asset for design engineers, practitioners and researchers. * The structure of the book and the nature of its chapters also make it suitable for a newcomer to the field.
The integration of process design and control Summary and future directions. -- Part A-Controllability analysis and process characterisation. -- Part B-Integrated process design and control Methods. -- Part C-Plantwide interactions of design and control. -- Part D-Integrated process design and control Extensions.
Includes bibliographical references and subject and author indexes.
Keywords: Chemical process control; Chemical engineering -- Automation; Chemical plants -- Design and construction; Chemical process control. Chemical engineering -- Automation. Chemical plants -- Design and construction; Electronic books